Patient safety climate in 92 US hospitals: differences by work area and discipline - Singer, Sara J; Gaba, David M; Falwell, Alyson; Lin, Shoutzu; Hayes, Jennifer; Baker, Laurence (Medical care, 2009)
Concern about patient safety has promoted efforts to improve safety climate. A better understanding of how patient safety climate differs among distinct work areas and disciplines in hospitals would facilitate the design and implementation of interventions. To understand workers' perceptions of safety climate and ways in which climate varies among hospitals and by work area and discipline. We administered the Patient Safety Climate in Healthcare Organizations survey in 2004-2005 to personnel in a stratified random sample of 92 US hospitals. We sampled 100% of senior managers and physicians and 10% of all other workers. We received 18,361 completed surveys (52% response). The survey measured safety climate perceptions and worker and job characteristics of hospital personnel. We calculated and compared the percent of responses inconsistent with a climate of safety among hospitals, work areas, and disciplines. Overall, 17% of responses were inconsistent with a safety climate. Patient safety climate differed by hospital and among and within work areas and disciplines. Emergency department personnel perceived worse safety climate and personnel in nonclinical areas perceived better safety climate than workers in other areas. Nurses were more negative than physicians regarding their work unit's support and recognition of safety efforts, and physicians showed marginally more fear of shame than nurses. For other dimensions of safety climate, physician-nurse differences depended on their work area. Differences among and within hospitals suggest that strategies for improving safety climate and patient safety should be tailored for work areas and disciplines.